ISLAMIC RELIGIOUS EDUCATION AND ANTI-CORRUPTION ISSUES - solikul hadi (Pondok Pesantren Modern Islam Assalaam, 2021)
Corruption has always been a trending topic that is timeless, starting from the colonial era, the Company to the era of freedom of argument. Problems that arise in Indonesia range from poverty rates, lack of equal distribution of education to deviant behavior due to the greed of someone who does not belong to him (corruption). The act of corruption is driven by several factors, including the factor of a person’s inability to control himself. So in this study, it is necessary to have an anticorruption attitude that is instilled in students from an early age through an educational institution. The purpose of this study was to find out how to include anti-corruption values in Islamic religious learning in educational institutions. The method used in this research is qualitative research, where this research comes from various references that can be used as materials or sources to solve problems. This qualitative research focuses on the study of text in terms of content, meaning, structure and discourse. The results of this study show that the design of Islamic Religious Education and the issue of anti-corruption is by inserting anti-corruption material into the existing material on KI and KD. The insertion of anti-corruption material for students to be able to analyze existing problems in reality using the Islamic perspective or perspective of the movement contained in the Koran and as-sunnah. To participate in the movement to eradicate and prevent corruption, there are two models, namely, the educational process must foster socio-normative concern, build objective reasoning and develop universal perspectives on individuals and education must lead to strategic seeding, namely individual personal qualities that are consistent and strong in role involvement social.